LESSONS IN GRADE 11 MATHEMATICS USING GRAPHING CALCULATOR APPLICATIONS - Balantes, Cristian Mark B; Tonga, Daves L (PEOPLE: International Journal of Social Sciences, 2020)
Since mobile devices are becoming ubiquitous in today’s student generation and to replace bulky and costly handheld graphing calculators, this quasi-experimental study determined the effects of the lessons using graphing calculator applications in a Mathematics classroom. The study involved two intact classes of Grade 11 GAS students of San Jose National High School, Malilipot, Albay. The experimental group was taught lessons using graphing calculator applications with the integration of contextualized, inquiry-based, collaborative and interactive learning approaches. On the other hand, the control group received the same lessons but without the use of applications. The actual conduct of the lessons was video-recorded and observed by the teacher-observers to determine and analyze carefully the students’ notable behaviors. Further, the effects of the lessons in terms of students’ performance, mental effort, and interest were assessed by using teacher-made test, Paas Mental Effort Rating (PMER) scale, and Mathematics Interest Inventory, respectively. Students’ journal entries, teachers’ observation notes, and focus group discussions’ responses were used to triangulate the results. Qualitative and quantitative analyses showed that the lessons using graphing calculator applications supported student collaboration and facilitated better teacher-student interaction. It also allowed students to become comfortable when and how to use the applications, as well as making them active and participative during learning activities. It further enhanced students’ conceptual understanding and process skills, and increased their level of interest towards Mathematics. The use of the applications also afforded the minimizing of students’ extraneous cognitive load by investing lower mental effort in learning the lessons. To this extent, the use of graphing calculator applications in Mathematics lessons is needed for the betterment of learning the subject.